Investigation into The Filterability of Raw Sugars from Different Geographical Regions of The World - Korea, Kanada . T.; Suleiman, Kamal; Mohammed, Amin Yousif; Ahmed, Omer (Gezira Journal of Engineering and Applied Sciences, 2018)
This  study  was  carried  out  at  Al khaleej  Sugar  Refinery  in  Dubai, United   Arab   Emirates.  The  study  aimed  to  find  out  the  correlation  between  the  filterability  and  slurry  resistance  values  of   raw  melt  liquor  in  the  carbonation sugar  refinery  and   the  raw  sugar  quality.  The investigation utilized 5 raw sugar samples collected from various regions of the world comprising three quality groups namely; Low Pol sugar (LP) from Thailand, Very High Pol sugar (VHP)   from  Brazil , South-Africa , Sudan , India , and  Very  Very High Pol  sugar ( VVHP )    from  Brazil. The  filterability  and  the  slurry  resistance  tests  were  used  as the main determining factors for the evaluation. The  filterability  of  refined  sugar  (considered  as 100 % ) was  used  as  a reference  value  for comparison. The  results  of  the  experiments  showed  that  the  filterability  of (L P)  raw  sugar  was only about 20% from that of  refined sugar. Whereas the filterability  values  for  (VHP) and  (VVHP) sugars  ranged  between 40% to 80%  from  that  of  refined  sugar.  In addition, the  slurry  resistance  values  for  VHP  and VVHP  sugars  in the  laboratory  were  0.76  and  0.64  respectively  compared  to 0.74 and 0.48  in  the  refinery  production line. It was also observed that there is a close similarity between laboratory filterability and slurry resistance with the actual refinery filtration process which suggests that the laboratory filterability and slurry resistance tests could  be  used  as tool to predict the  behavior  of  the refinery  filtration process  for  similar  qualities  of  raw  sugar.